Asistensi Implementation of Database-Based CodeIgniter PHP Framework on School Alumni Data (Case Study of Alumni Data for SMK Taman Siswa Medan) - Aripin Rambe (Sean Institute, 2022)
By using the CodeIgniter PHP framework, an information system web application software can be created to help manage data. In this study, software was developed to help manage school alumni data. By using the security layer in the CodeIgniter PHP framework, data filtering can be done to prevent the exploitation of security vulnerabilities, which include Cross-site Scripting (XSS) and SQL Injection. This can be seen from the test results that only produce low level warnings. So the quality of the software developed in terms of security is quite good.